10×{4^2×4^6×4^5-3×[7×7^4:7^3-(5^2)^5:5^8-3]}
Răspunsuri la întrebare
Răspuns de
8
10×{4^2×4^6:4^5-3×[7×7^4:7^3-(5^2)^5:5^8-3]}=
10×[4^8 : 4^5 - 3 × (7^5 : 7^3 - 5^10 : 5^8 - 3)] =
10 × [ 4^3 - 2 × ( 7^2 - 5^2 - 3)] =
10 × [4^3 - 2 × ( 49 - 25 - 3)] =
10 × ( 64 - 2 × 21) =
10 × ( 64 - 42) =
10 × 22 =
220
_____
10×[4^8 : 4^5 - 3 × (7^5 : 7^3 - 5^10 : 5^8 - 3)] =
10 × [ 4^3 - 2 × ( 7^2 - 5^2 - 3)] =
10 × [4^3 - 2 × ( 49 - 25 - 3)] =
10 × ( 64 - 2 × 21) =
10 × ( 64 - 42) =
10 × 22 =
220
_____
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă